Relationship of Self-Image with Interpersonal Communication of Vocational Students - Ranisa Putri Kemala; Indah Sukmawati (Universitas Negeri Padang, 2019)
Students at school should be able to build good social relationships with others, because one of the tasks of student development is being able to one of them play a role in social life such as developing interpersonal communication both individuals and groups. One of the things that influences interpersonal communication is a stable self-image. But still found in the field of students who are awkward in communicating. This study aims to empirically examine the relationship of self-image with interpersonal communication in students of SMK N 9 Padang. This research is a descriptive correlational research with quantitative methods. Sampling in this study used stratidfied random sampling technique with a total sample of 295 students of SMK N 9 Padang. The research instrument used was a self-image questionnaire and an interpersonal communication questionnaire. The results revealed that the self-image of students at SMK N 9 Padang was mostly in the quite good category and interpersonal communication of students of SMK N 9 Padang was mostly in the quite good category. There is a significant relationship between self-image and students' interpersonal communication at SMK N 9 Padang.